Multidrug resistance Acinetobacter species in ventilator associated pneumonia patients in MICU - Iravane, Jyoti A.; Harbade, Mangala S.; Shaji, Eby P.; Onkari, Amruta (International Journal of Research in Medical Sciences, 2024)
Background: Ventilator associated pneumonia (VAP) is defined as pneumonia that develops 48-72 hours after endotracheal intubation and is characterized by the presence of a new or progressive infiltrate, symptoms of systemic infection, respiratory distress, and the microbiological discovery of a causal agent. There is a substantial attributable death rate linked to VAP caused by Acinetobacter species. Methods: A hospital-based retrospective study was conducted from June 2023 to June 2024 at GMCH, Aurangabad. Six hundred thirteen (613) endotracheal aspirate samples were obtained from patients admitted in intensive care unit. Semi-quantitative processing of the samples was done using accepted microbiological methods. According to CLSI guidelines, antimicrobial susceptibility testing was done. Results: Out of 613 samples, organism isolated were Acinetobacter baumannii, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumonia, and Enterobacter cloacae. Thirty-seven (37) VAP cases were found from 613 samples; sixteen (16) of them (43%) developed VAP as a result of multidrug resistant (MDR) Acinetobacter baumannii. Eleven (69%) of the sixteen VAP cases exhibited minocycline sensitivity. Nine out of 16 VAP cases (56%) had a fatal outcome as a result of the MDR Acinetobacter species. Conclusions: According to this study, minocycline is the most effective drug against MDR Acinetobacter species. To lower mortality and morbidity in VAP patients, it is important to identify the organism and follow IPC procedures, which include hand hygiene techniques, bundle care approach, disinfections, screening of the patient's environment, development of an antimicrobial stewardship program, and frequent surveillance.